In Situ Determination of Interfacial Energies between Heterogeneously Nucleated CaCO3 and Quartz Substrates: Thermodynamics of CO2 Mineral Trapping - Fernandez-Martinez, Alejandro; Yandi Hu; Lee, Byeongdu; Jun, Young-Shin*; Waychunas, Glenn A*. (Environmental Science & Technology, 2013)
The precipitation of carbonate minerals—mineral trapping—is considered one of the safest sequestration mechanisms ensuring long-term geologic storage of CO2. However, little is known about the thermodynamic factors controlling the extent of heterogeneous nucleation at mineral surfaces exposed to the fluids in porous reservoirs. The goal of this study is to determine the thermodynamic factors controlling heterogeneous nucleation of carbonate minerals on pristine quartz (100) surfaces, which are assumed representative of sandstone reservoirs. To probe CaCO3 nucleation on quartz (100) in solution and with nanoscale resolution, an in situ grazing incidence small-angle X-ray scattering technique has been utilized. With this method, a value of α′ = 36 ± 5 mJ/m2 for the effective interfacial free energy governing heterogeneous nucleation of CaCO3 has been obtained by measuring nucleation rates at different solution supersaturations. This value is lower than the interfacial energy governing calcite homogeneous nucleation (α ≈ 120 mJ/m2), suggesting that heterogeneous nucleation of calcium carbonate is favored on quartz (100) at ambient pressure and temperature conditions, with nucleation barriers between 2.5% and 15% lower than those expected for homogeneous nucleation. These observations yield important quantitative parameters readily usable in reactive transport models of nucleation at the reservoir scale.